2022
DOI: 10.1001/jamanetworkopen.2022.13553
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Status Among Adults Admitted to Intensive Care Units in Veneto, Italy

Abstract: This cohort study examines admissions to intensive care units for COVID-19–associated acute respiratory distress syndrome by COVID-19 vaccination status among adults in the Veneto region of Italy from May to December 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 8 publications
6
20
0
2
Order By: Relevance
“…Our analyses, similar to previously published data, [19][20][21] show that the risk of ICU admission for COVID-19 pneumonia in vaccinated individuals was 15% of the risk of unvaccinated individuals, meaning that being unvaccinated resulted in almost 7-times higher risk of being admitted to an ICU.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our analyses, similar to previously published data, [19][20][21] show that the risk of ICU admission for COVID-19 pneumonia in vaccinated individuals was 15% of the risk of unvaccinated individuals, meaning that being unvaccinated resulted in almost 7-times higher risk of being admitted to an ICU.…”
Section: Discussionsupporting
confidence: 89%
“…6,[21][22][23][24][26][27][28][29][30] Even 4 months after vaccine administration, vaccinated individuals still had a 4.5-times lower risk of ICU admission compared with unvaccinated individuals. Furthermore, mRNA vaccines maintained a greater and more prolonged effectiveness in preventing ICU admission compared with AdV.During the vaccination campaign, Lombardy experienced 2 pandemic waves.…”
mentioning
confidence: 99%
“…A recent cohort study conducted in a northern region of Italy reported a 18% rate of vaccinated patients admitted to the ICU, with a median time from vaccination to ICU admission of 5 to 6 months ( 14 ). Another multicenter observational study, conducted in Spain from January to September 2021, reported that only 7% of patients admitted to the ICU for severe COVID-19 was vaccinated ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are different by our results. Firstly, the study by Lorenzoni et al ( 14 ) was conducted from May to December 2021, when only the 57.5% of the total population in Italy received at least one dose of anti-SARS-CoV-2 vaccine ( 28 ). Similarly, the Spanish study was conducted in the same period and the 69% of Spanish inhabitants were vaccinated ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation